2006
DOI: 10.1111/j.0030-1299.2006.14183.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in body weight and wing length among some British passerine birds

Abstract: du Feu, R. 2006. Recent changes in body weight and wing length among some British passerine birds. Á/ Oikos 112: 91 Á/101.We tested the prediction that global warming has caused recent decreases in body weight (Bergmann's rule) and increases in wing length (Allen's rule) in 14 species of passerine birds at two localities in England: Wicken Fen (1968Á/2003) and Treswell Wood (1973Á/2003.Predicted long-term linear decreases in residual body weight occurred in four species: dunnocks (Wicken Fen), and great tits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
114
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 39 publications
8
114
2
Order By: Relevance
“…continued plant growth during mid-winter, fewer and shorter periods when foraging sites freeze over). This interpretation is consistent with that of Kaňuščák et al (2004) for River Warbler (Locustella fluviatilis) and of Yom-Tov et al (2006a) for Blackbird. In this context, it is worth noting that improved body condition was also observed over the last decades for Teal wintering in Essex, UK (R. King, unpublished data) suggesting this is a largescale change consistent with a global temperature increase.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…continued plant growth during mid-winter, fewer and shorter periods when foraging sites freeze over). This interpretation is consistent with that of Kaňuščák et al (2004) for River Warbler (Locustella fluviatilis) and of Yom-Tov et al (2006a) for Blackbird. In this context, it is worth noting that improved body condition was also observed over the last decades for Teal wintering in Essex, UK (R. King, unpublished data) suggesting this is a largescale change consistent with a global temperature increase.…”
Section: Discussionsupporting
confidence: 89%
“…Increase in mean body size at the population level has been demonstrated in some species Yom-Tov 2004, 2005;Yom-Tov et al 2008; review in Millien et al 2006), though the opposite has also been reported (e.g. Smith et al 1998;Yom-Tov 2001;Yom-Tov et al 2006a). Increased body mass has been reported in wild bird populations, probably a combined effect of greater food availability and lower energy demands (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, research on many indicator species has become increasingly important. Within the last decades, many migrant passerines have changed in their migration phenology (Cotton 2003, Lehikoinen et al 2004, Crick and Sparks 2006, Zalakevicius et al 2006, moulting (Hedenström et al 2007), the timing of breeding (Crick et al 1997, Forchhammer et al 2002, Both et al 2004, distribution factors (Berthold 1993, Crick 2004, Seather et al 2004) and biometrics (Yom-Tov et al 2006), presumably due to climatic factors (Williamson 1975, Lundberg and Edholm 1982, Berthold 1990). Short-and medium-distance migrants adapt more quickly to changed conditions than long-distance migrant species subjected to stronger genetic controls (Berthold 1996, Pulido et al 2001, Butler 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively simple techniques of measuring the wing length compared to the tail length or wing formula, allow to collect data useful for various studies concerning long-term changes, climate changes, populations, sex and age differentiation, adaptation for migration, timing of migration (e.g. Busse 1968Busse , 1988Busse , 1997Busse , 1999Busse and Maksalon 1986;Lo Valvo et al 1988;Tellería and Carbonell 1999;Nowakowski 2000Nowakowski , 2002Tellería 2001, 2002;Yom-Tov et al 2006;Zaniewicz and Busse 2008;Salewski et al 2010;Van Buskirk et al 2010;Kovács et al 2010Kovács et al , 2012Arizaga et al 2012). However, clear dependencies are usually hidden, as the variation in wing length depends on several factors, such as sex, age, population, status of the specimen (skin, live bird) (Svensson 1992, Jenni and Winkler 1994, Fiedler 2005.…”
Section: Introductionmentioning
confidence: 99%